Security Analysis of An Image Encryption Algorithm Based on Chaos and DNA Encoding - Ozkaynak, Fatih; Ozer, Ahmet Bedri; Yavuz, Smna (IEEE, 2013)
Chaos and cryptography have some common features. Due to the close relationship, researchers try to combine the chaotic system with cryptosystem. Despite the many proposals that use various methods in the design of encryption algorithms, there is a definite need for a mathematically rigorous cryptanalysis of these designs. In this study, we analyze the security weaknesses of an image encryption algorithm based on DNA encoding and chaos. By applying chosen-plaintext attacks, we show that all the secret parameters can be revealed.
Keywords: chaos; cryptography; DNA encoding; cryptanalsis; CRYPTANALYSIS; Engineering; Telecommunications